THE EFFECTIVENESS OF SCIENCE LITERACY CULTURE THROUGH ENCYCLOPEDIC TEACHING MATERIALS IN SCIENCE LEARNING AT ELEMENTARY SCHOOLS IN WEST JAKARTA - Erdhita Oktrifianty; Rizki Zuliani; Een Unaenah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This study emphasized on the importance of teaching materials to improve the culture of scientific literacy in science learning through encyclopedic books. Thus, there was a scientific literacy among students and between teachers and students through a teaching material. The encyclopedic teaching materials were tailored to the students' interests aiming to create a culture of scientific literacy. The purpose of this study was to determine the learning outcomes and scientific literacy abilities of fifth grade students after using encyclopedic teaching materials. The research method used in this study was action research in which the researchers acted as collaborators while teachers as implementers of action. This study was conducted at 3 elementary schools in West Jakarta. The object was the science subject at grade V of elementary school which was developed in the form of encyclopedic teaching materials. This study resulted in an increase in science learning especially about human movement system, human respiratory system, and human circulatory system,  which utilized an encyclopedic teaching materials. It was recommended that teachers could cultivate the students’ literacy through encyclopedic teaching materials on other subjects in order to facilitate students in the learning process.